Posology adjustments of oral antineoplastic agents for special populations: patients with renal impairment, hepatic impairment and hematologic toxicities. Issue 6 (3rd June 2018) - González, Julieta; Quiroga, Matías; Escudero-Vilaplana, Vicente; Collado-Borrell, Roberto; Herranz-Alonso, Ana; Sanjurjo Sáez, María
ABSTRACT: Background : Oral antineoplastic agents (OAA) have reached 30–50% of all antineoplastic treatments. Although they seem safer than parenteral therapy, many severe problems can occur if the dose is not adequately adjusted in special situations. Our objective is to create a comprehensive guide with dosage adjustment recommendations for OAA in cases of renal and hepatic impairment and hematologic toxicities. Research design and methods : We analyzed all OAA approved by EMA in July 2017. We assessed data related to dose adjusted from the FDA's and EMA's summary of product characteristics. Results : 53 OAA were analyzed. We identified 44 (83%) OAA requiring dosage adjustments in special situations: 20 (37.7%) in renal impairment, 37 (69.8%) in hepatic impairment, and 22 (41.5%) in patients with hematologic toxicity. The dose adjustment recommendations varied in 31 (58.5%) OAA between the FDA and EMA. Detailed recommendations for each OAA were collated into comprehensive tables. Conclusions : Most OAA have to be adjusted in special situations. Given the number of OAA available for different indications, this review can serve as an easy tool to help health professionals dose these complex treatments.